Bach's changing world : voices in the community - Baron, Carol (Eastman studies in music, 2006)
"Bach's Changing World: Voices in the Community studies the community in which Bach spent the last, longest, and most prestigious part of his life: the Leipzig middle class. These essays by prominent musicologists and scholars of religious history and German culture highlight the dynamic religious, social, and political forces that emerged during the composer's lifetime. Using entertainment venues and all forms of commercially produced and distributed literature - "popular" in that world - as well as "official" documents, they explore Leipzig's distinctive middle-class public culture. Contemporary thought was fragmented, intellectually complex, and unable to assimilate the multiplicity of ideas, beliefs, and values that were simultaneously current